Evaluating Income Distribution of Certified and Non-Certified Coffee Farmers in West Lampung Regency - Rahmita Zahra Asyifa; Handoyo Mulyo Jangkung; Irham (E3S Web of Conferences, 2023)
Income distribution needs greater attention because an uneven distribution of income can leave farmers in a more vulnerable position to the effects of production risk. Many prior studies have focused on the impact of certification on income levels and limited focus on its effect on income distribution. Therefore, this study aims to compare the income distribution of certified and non-certified coffee farmers in West Lampung Regency, which was purposively chosen due to its status as the largest producer of coffee in Lampung Province. Using convenient sampling, 140 coffee farmers were surveyed, consisting of 70 farmers with and 70 without certifications. The data was analysed using the Gini ratio and World Bank’s version analysis. The findings showed that the income distribution for coffee farming and household income distribution was even by Gini ratio approaches. Similarly, with the World Bank’s version, coffee farming and household income distribution are classed as low inequality. In contrast with coffee farming and household income distribution, income outside of coffee farming distribution was unevenly distributed, showing that side jobs have a negative bias toward income distribution. These results suggest that the benefits provided to certified coffee farmers, such as regular training, contributed to coffee farmers’ income equity.